2004
DOI: 10.1080/10640260590893593
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Personality Disorders Among Those with Eating Disorders

Abstract: The genuine prevalence of personality disorders among those with eating disorders is unknown. However, in this paper, we summarize the existing data, with careful acknowledgment of our approach to interpretation as well as the limitations of previous studies. Our findings indicate that obsessive-compulsive personality is the most common personality disorder in restricting-type anorexia nervosa, while borderline personality is the most common personality disorder in binge-eating/purging type anorexia nervosa. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 34 publications
9
90
4
3
Order By: Relevance
“…There is substantial evidence of comorbidity between the eating disorders and the personality disorders, with high levels of borderline personality disorder diagnosed among eating disorder patients who binge and purge, obsessive-compulsive and avoidant personality disorders among more restrictive patients, and avoidant personality disorder among patients with binge eating disorder (e.g., Raymond et al, 2005;Sansone et al, 2006). However, the personality disorders commonly co-occur (Dolan et al, 1995).…”
Section: Personality Disorder Cognitions In the Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence of comorbidity between the eating disorders and the personality disorders, with high levels of borderline personality disorder diagnosed among eating disorder patients who binge and purge, obsessive-compulsive and avoidant personality disorders among more restrictive patients, and avoidant personality disorder among patients with binge eating disorder (e.g., Raymond et al, 2005;Sansone et al, 2006). However, the personality disorders commonly co-occur (Dolan et al, 1995).…”
Section: Personality Disorder Cognitions In the Eating Disordersmentioning
confidence: 99%
“…For example, using the Personality Beliefs Questionnaire (PBQ - Beck & Beck, 1991), Connan et al (2009) demonstrated that eating pathology is more strongly associated with the cognitive element of avoidant and obsessive-compulsive personality disorder pathology than with borderline personality disorder. They hypothesized that the apparent link with borderline personality pathology in other research (e.g., Sansone et al, 2006) might be due to anxiety cognitions underlying the borderline personality disorder features in many cases. This finding supports an alternative approach to understanding the eating disorder-personality link, which is to focus at the level of personality pathology as it naturally clusters, rather than in terms of diagnostic categories.…”
Section: Personality Disorder Cognitions In the Eating Disordersmentioning
confidence: 99%
“…A meta-analysis (Sansone et al 2005) of four ED groups-AN-restricting (AN-R), AN-bingeing (AN-B), BN, and binge eating disorder (BED)-revealed interesting comorbidity patterns with PDs in all three clusters. Avoidant PD was comorbid with all types of ED, whereas BN showed the strongest comorbidity across the PD domain.…”
Section: Comorbidity With Eating Disordersmentioning
confidence: 99%
“…Rastam (1992) a révélé une forte association entre l'anorexie et le trouble de la personnalité obsessionnelle-compulsive (TPOC). Pour les deux types d'anorexie mentale, les TP les plus fréquents sont ceux du groupe C. Sansone et al (2005) ont ajouté que le TP limite était plus associé aux TA avec symptômes boulimiques (ANBP et BN) qu'à l'ANR. Thornton et Russell (1997) ont démontré que 35 % des patientes anorexiques présentaient un TPOC prémorbide.…”
Section: Troubles De La Personnalitéunclassified